From the hypertransaminasemia symptoms to the recognition of late-onset Pompe disease in a 12-year-old boy - Ewa Grzywna; Jarosław Kwiecień (Termedia Publishing House, 2021)
The paper presents the case of a 12-year-old boy hospitalised due to persistent hypertransaminasemia of unknown origin, in whom rare metabolic disease - Pompe disease, was finally diagnosed. We discuss the possible symptoms and the diagnostic criteria for Pompe disease, as well as modern genetic methods of diagnosing. The importance of including this metabolic disease in differential diagnosis of hypertransaminasemia was underlined. The recombinant human α-glucosidase as the enzyme replacement therapy makes nowadays the early diagnosis of Pompe disease especially important.